2021
DOI: 10.1186/s12879-021-05918-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection and its associated factors among medical waste collectors at public health facilities in eastern Ethiopia: a facility-based cross-sectional study

Abstract: Background The risk of hepatitis B virus infection among medical waste handlers who undergo collection, transportation, and disposal of medical wastes in the health institutions is higher due to frequent exposure to contaminated blood and other body fluids. There is limited evidence on the seroprevalence of hepatitis B among medical waste handlers in eastern Ethiopia. The study was aimed at studying the seroprevalence of Hepatitis B Virus and associated risk factors among medical waste collecto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…Similar study by by Al-Marrani and Al-Shamahy 14 found that HBV and HCV were detected in 8.2% and 1.03% of them respectively. Also, Mengiste et al, 1 documented that the HBsAg was 20.4% reported in eastern Ethiopia. Also, the HBsAg and anti-HCV, respectively, were detected at 1.3% and 0.7% in southern Ethiopia 16 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Similar study by by Al-Marrani and Al-Shamahy 14 found that HBV and HCV were detected in 8.2% and 1.03% of them respectively. Also, Mengiste et al, 1 documented that the HBsAg was 20.4% reported in eastern Ethiopia. Also, the HBsAg and anti-HCV, respectively, were detected at 1.3% and 0.7% in southern Ethiopia 16 .…”
Section: Discussionmentioning
confidence: 95%
“…Medical waste handlers are high exposure to infectious agents throughout the waste collection, segregation, storage, transportation, and final removal of all types of waste that carry a high potential for infection 1 . Exposure of medical waste handlers to infectious agents is the most common problem worldwide that happens as a result of poor medical waste management practices in developing countries 2, 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, mishaps from injection needles are quite common worldwide ( Liyew et al , 2020 ). Moreover, safe disposal challenges for sharps materials are a perennial problem in sub-Saharan Africa and increase the risk of transmission of infectious diseases ( Mengiste et al , 2021 ). While disposal requirements for RemovAid™ are not averted, the blade is not exposed like that of a scalpel and is not easily used for other purposes; in addition, a reusable product for sterilization is theoretically feasible, but would need to be investigated in a future study.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Related research conducted in public health facilities in eastern Ethiopia, where 20% of the study participants had HBV infection, provided support for this conclusion. 21 …”
Section: Introductionmentioning
confidence: 99%